Effect of body mass index on peak growth hormone level after growth hormone stimulation test in children with short stature - Na Yeong Lee; Sung Eun Kim; Seulki Kim; Moon Bae Ahn; Shin Hee Kim; Won Kyoung Cho; Kyoung Soon Cho; Min Ho Jung; Byung-Kyu Suh (Korean Society of Pediatric Endocrinology, 2021)
Purpose The aim of this study is to evaluate the effect of body mass index (BMI) on peak serum growth hormone (GH) level after GH stimulation test in children with short stature. Methods Data were obtained from retrospective medical record reviews of those who visited the pediatric endocrine clinic at St. Vincent's Hospital of Catholic University for short stature from January 2010 to June 2019. A total of 115 children (66 boys and 49 girls) whose height was less than the third percentile according to age and sex underwent GH stimulation testing. Results Of the 115 subjects, 47 were diagnosed with GH deficiency (GHD) and 68 were diagnosed with idiopathic short stature (ISS). In patients with GHD, weight standard deviation score (SDS) (P<0.001) and BMI SDS (P≤0.001) were higher, and free thyroxine (T4) level (P=0.012) was lower than those in the ISS group. In total subjects, peak serum GH level after GH stimulation test showed negative correlations with weight SDS (r=-0.465, P<0.001), BMI SDS (r=-0.398, P<0.001), and thyroid stimulating hormone (r=-0.248, P=0.008) and a positive correlation with free T4 (r=0.326, P<0.001). In multiple regression analysis, BMI SDS (P=0.003) was negatively associated with peak serum GH level in GH stimulation testing after adjusting for age, sex, pubertal status, and type of pharmacological stimulus. Conclusions The BMI SDS influences peak serum GH level after GH stimulation testing. We should consider BMI factors when interpreting the results of GH stimulation testing.